1993
DOI: 10.5636/jgg.45.79
|View full text |Cite
|
Sign up to set email alerts
|

A Phase-Transition Model for Geomagnetic Polarity Reversals.

Abstract: It is generally considered that the polarity reversal intervals have an exponential distribution. We have examined the distribution using all reversal data back to about 165 m.y. ago, and found that this distribution follows a power-law rather than an exponential. Power laws are common in critical phenomena, and therefore we propose that the geodynamo is marginally stable and that the geomagnetic polarity reversal is a kind of critical phenomenon.We present a simple model in which turbulent eddies in the outer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 19 publications
4
21
0
Order By: Relevance
“…He concluded, however, that the apparent scaling does not warrant selfsimilarity and demonstrated that the non-stationary Poisson model (McFadden and Merrill, 1984;Lutz and Watson, 1988) provides an adequate description for the distribution of interval lengths. Seki and Ito (1993) obtained a similar result to Gaffin (1989), but interpreted the power law distribution as an evidence of the dynamical phase-transition state of geodynamo.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…He concluded, however, that the apparent scaling does not warrant selfsimilarity and demonstrated that the non-stationary Poisson model (McFadden and Merrill, 1984;Lutz and Watson, 1988) provides an adequate description for the distribution of interval lengths. Seki and Ito (1993) obtained a similar result to Gaffin (1989), but interpreted the power law distribution as an evidence of the dynamical phase-transition state of geodynamo.…”
Section: Introductionsupporting
confidence: 54%
“…The model in Seki and Ito (1993) has a similar to Sornette's model feedback mechanism and exhibits critical behavior like the power-law distribution of the polarity reversal intervals. The behavior of model, however, differed from that of geomagnetic data in the power exponent being −0.5, while the power exponent obtained from geomagnetic data was −1.5.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Seki & Ito [ 1993] proposed that the scaling property of the polarity reversal data could be evidence of a near critical configuration tbr the geodynamo. Using a simple model (a Q2R dissipative model), they clearly noted that the model selforganizes to a critical configuration independently of the initial conditions, showing a power law distribution of the polarity intervals, when energy dissipation, accompanying polarity reversals, is taken into account.…”
Section: Data Description and Analysismentioning
confidence: 99%